Clinical and Genetic Characteristics of 23 Korean Patients with Haploinsufficiency of the Short-stature Homeobox-containing Gene - Lee, Jeong-Seon; Kim, Hwa Young; Lee, Young-Ah; Lee, Seong-Young; Cho, Tae-Joon; Ko, Jung Min (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background The short-stature homeobox-containing gene (SHOX) is one of the major growth genes in humans. The clinical spectrum of SHOX haploinsufficiency ranges from Léri–Weill dyschondrosteosis to idiopathic short stature. Herein, we describe the clinical and genetic characteristics of 23 Korean patients with SHOX deficiency disorders.Methods Medical records of 23 patients (19 females and 4 males) from 15 unrelated families who were genetically confirmed to have SHOX deficiency were retrospectively reviewed. SHOX gene deletions or mutations were determined by sequence analyses using multiplex ligation-dependent probe amplification, chromosomal microarray, and/or Sanger sequencing methods.Results In the 15 families, 9 probands were de novo cases. All 23 patients showed mesomelia. Madelung deformity and tibia vara were observed in 13 (56.5%) and 3 (13.1%) patients, respectively. Genetically, 11 (73.3%) of the 15 families showed SHOX deletions of various sizes, and the other 4 families harboured SHOX sequence variants. Four patients had undergone orthopaedic surgeries (3 for tibia vara and 1 for Madelung deformity). Among 7 patients who had received growth hormone treatment for ≥1 year, 5 showed good responses, with a median first-year change-in-height standard deviation score of +0.6. There were no significant differences in the clinical characteristics of the deletion and point mutation groups.Conclusions A high index of suspicion and the genetic confirmation of SHOX deficiency are helpful for the timely management of the condition and are needed to provide genetic counselling to the family members of the patients.
Keywords: SHOX deficiency; Léri-Weill dyschondrosteosis; haploinsufficiency; Madelung deformity; mesomelia